The Influence of Self-Confidence on Students’ Speaking Ability: A Correlational Study at MA Nurul Muttahidah Pinotu - Shaleha, Anisatun; Mukrim, Mukrim; Lebagi, Desrin; Hasyim, Zarkiani (Universitas Pahlawan Tuanku Tambusai, 2025)
Self-confidence plays a crucial role in second language learning, particularly in enhancing speaking ability. In many senior high schools in Indonesia, English is taught as a foreign language (EFL), and students often struggle with speaking due to low self-confidence. This study investigates the correlation between self-confidence and speaking ability among eleventh grade students at MA Nurul Muttahidah Pinotu. Employing a quantitative research approach with a correlational design, the study involved 25 students as the total sample. The instruments used were a self-confidence questionnaire consisting of 20 items based on a Likert scale and a speaking test assessing five aspects: pronunciation, vocabulary, grammar, fluency, and comprehension. The data were analyzed using SPSS version 24, including normality and linearity tests, followed by Pearson Product Moment correlation analysis. The results revealed a statistically significant positive correlation (r = 0.505, p = 0.010) between students’ self-confidence and their speaking ability. This finding suggests that the more confident students are, the better their speaking performance. However, the small sample size is a limitation of this study, and further research with larger samples is recommended. These results highlight the importance of fostering students’ self-confidence to improve speaking skills in EFL contexts, especially in underrepresented educational settings such as senior high schools.